Super Turbo and the fountain of doom - Powers, Edgar J. (Powers, Edgar J. Super Turbo graphic novels, 2023)
"The Superpet Superhero League has finally figured out how to reach the water fountain! Now they can stay cool and hydrated without battling Whiskerface and his Rat Pack when they go to the cafeteria for snacks! But as soon as the last superpet has taken their turn at the fountain, they realize they have a big problem. The water won't stop flowing. Could this actually be the terrifying Fountain of Doom? Can the superpets stop the fountain from flooding the school? And which of the pets can even swim?!" --